Institutions, myths and utopias. Conceptual relationships in the transcendental thought of Franz Hinkelammert - HERRERA TORRES , Hugo (Utopía y Praxis Latinoamericana, 2025)
The objective of the paper is to identify the conceptual relationships between institutions, myths and utopias in Hinkelammert's reflection on transcendental scenarios. The author, despite delving into the study of institutions, myths and utopias, which are three types of transcendental scenarios, does not explicitly establish their technical links, although some links are implicitly perceived. These scenarios go through the concrete reality of human beings. The incorporation of these then becomes necessary in the analyzes of empirical sciences. The results of the article indicate that the three types of scenarios, together, constitute an explanatory framework that helps understand past and current social dynamics. Myths provide the orientation of utopias, which are formally reflected in institutions. The behaviors of subjects in societies are precisely determined by institutions. Myths, consequently, are the starting point for the construction of social orders.